Fraud Factor Analysis Hexagon in Detecting Financial Report Fraud In Listed Companies in Indonesia: A Systematic Literature Approach - Devia Putri Hascika; Debora Parlina Sinurat; Anisyah Vitriyah Dewi; Deni Sunaryo; Septantri Shinta Wulandari (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Financial reporting fraud is a significant challenge across industries, undermining stakeholder trust and the reliability of financial data. The Fraud Model Hexagon expands upon earlier models, like the Fraud Triangle and Fraud Diamond, by introducing six elements pressure, opportunity, rationalization, capability, ego, and collusion that offer a comprehensive view of the factors enabling fraud. This literature review systematically examines the model's effectiveness in detecting financial fraud within Indonesian corporations, especially those listed on the Indonesia Stock Exchange or connected to political and governmental entities. Ten studies from 2018 to 2024 were analyzed, focusing on each Fraud Hexagon element's role in fostering fraud. Findings highlight that pressure, opportunity, and collusion are primary drivers of fraud in politically connected sectors, with capability and rationalization further facilitating fraud, while ego emboldens managers to act without fear of repercussions. The Fraud Hexagon provides a nuanced framework for risk assessment, prompting recommendations for stronger internal controls and ethical standards. It also serves as a valuable diagnostic tool for auditors and regulators, particularly in politically sensitive sectors. This study contributes to understanding the social and psychological dimensions of financial fraud and offers a foundation for future cross-industry research.